Relationship Fintech Development and the Performance of Financial Industry - Azelia, Faiza Nur; Nuryakin, Chaikal (Department of Management, Faculty of Economics and Business, Brawijaya University, 2025)
This study identifies the relationship between the fintech development and the performance of companies in the financial industry listed on the Indonesia Stock Exchange (IDX) from 2017-2023. This research uses the number of fintech firms as a proxy for fintech development and net profit margin, return on assets, and return on equity as proxies for company performance. Utilizing the One Step Estimator Arellano-Bond model, the analysis reveals a significant impact of the number of fintech firms on the performance of companies in the financial industry, specifically within the non-bank sub-sector, as indicated by return on equity. The study concludes that an increase in the number of fintech firms in Indonesia can decrease the return on equity for companies in the financial industry and within the non-bank sub-sector. This effect is attributed to the high initial costs incurred from technology investments for financial firms to remain competitive.